2013
DOI: 10.1186/1936-6434-6-20
|View full text |Cite
|
Sign up to set email alerts
|

Evolution acceptance among pre-service primary teachers

Abstract: Background: The purpose of this study was to investigate evolution acceptance among pre-service primary teachers who opted to study biology (n=35). In this part of their teacher training course they were introduced to the theory of evolution. The study focused on (a) finding out the various degrees of evolution acceptance, (b) reasons behind these choices, (c) views on the origin and biodiversity of life and (d) the perceived impacts of evolution acceptance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(53 reference statements)
2
5
0
Order By: Relevance
“…So far, studies showed varying results, depending on the used instrument or the surveyed country. Results of some previous studies on university students of different European countries are supported by our findings (Arthur 2013;Beniermann 2019;Betti et al 2020;European Commission 2005;Gefaell et al 2020;Graf and Soran 2010;Großschedl et al 2014;Konnemann et al 2018;Nehm et al 2013;Southcott and Downie 2012). However, other studies revealed undecided positions or rejection of evolution among pre-service teachers in Greece and Turkey (Akyol et al 2010(Akyol et al , 2012Bilen and Ercan 2016;Deniz et al 2011;Deniz and Sahin 2016;Graf and Soran 2010;Irez and Bakanay 2011;Yüce and Önel 2015).…”
Section: Within the Group Of European First-year University Students Country Affiliation Plays Only A Minimal Role In Accepting Evolutionsupporting
confidence: 84%
“…So far, studies showed varying results, depending on the used instrument or the surveyed country. Results of some previous studies on university students of different European countries are supported by our findings (Arthur 2013;Beniermann 2019;Betti et al 2020;European Commission 2005;Gefaell et al 2020;Graf and Soran 2010;Großschedl et al 2014;Konnemann et al 2018;Nehm et al 2013;Southcott and Downie 2012). However, other studies revealed undecided positions or rejection of evolution among pre-service teachers in Greece and Turkey (Akyol et al 2010(Akyol et al , 2012Bilen and Ercan 2016;Deniz et al 2011;Deniz and Sahin 2016;Graf and Soran 2010;Irez and Bakanay 2011;Yüce and Önel 2015).…”
Section: Within the Group Of European First-year University Students Country Affiliation Plays Only A Minimal Role In Accepting Evolutionsupporting
confidence: 84%
“…The initial structure of the GAENE employed a four‐option response format (1 = Strongly Disagree to 4 = Strongly Agree). This ordinal‐option structure is in accord with the view of Carter and Wiles () that there are “various shades of evolution acceptance” that students take (Arthur, ; p. 7). We chose to have an even number of options in our first version so as to discourage large numbers of participants from choosing a neutral, “no opinion,” option to avoid deeper consideration, although we anticipated the need for changing to a 5‐option structure.…”
Section: Methodssupporting
confidence: 76%
“…I therefore use the term ‘creationism’ to represent specifically anti-evolutionary science stances. Several different authors have tried to outline differing scales and categories of evolution and creationism that encompass the wide range of versions of creationism (see Arthur, 2013; Scott, 2009). This kind of categorization is highly contested as these categories are not necessarily discrete nor definitive and do not entirely capture the range of possible perspectives or reflect the lived experience of individual’s understanding of the relationship between their own spiritual or religious belief and evolutionary science.…”
Section: Introductionmentioning
confidence: 99%